Análise do impacto dos aerossóis atmosféricos sobre fluxos radiativos numa região de transição Cerrado-Pantanal de Mato Grosso - Morais, Denes Martins de (2018)
During periods of drought the study region is influenced by aerosols from fires or anthropogenic actions, causing alteration in the radiative balance of the Earthatmosphere system. A series of data from 2001 to 2017 provided by the AERONET network of Cuiabá (Fazenda Miranda) was used in studies of optical depth (AOD), simple spreading albedo (SSA), extinction Angstrom exponent (EAE) and precipitable water. Well as, radiative forcing and radiative forcing efficiency, at the top and surface of the atmosphere. In 2007 we have the highest ODA intensity in the series, greater than 6. The dry season has higher mean AOD, EAE values close to 2 indicating fine particles, SSA ranging from 0.8 to 0.9 indicating spreader aerosol particles. Between the top forcing (FR TOP) and the surface (FR SUP), there is a minimum proportionality of 1/3. The FR TOP range being - 5 to - 52 Wm-2 , and the FR SUP of - 10 to - 180 Wm-2 . And with a radiative forcing of the atmosphere (FR ATM) ranging from 2 to 170 Wm-2 , positively. With a heating rate (RH) ranging from 0.05 to 0.28 K-1 . A linear correlation between radiative forcing at the top and surface with optical aerosol depth provided a 2nd-degree polynomial equation for AOD x FR SUP, and a 3rd-degree polynomial equation for AOD x FR TOP, for the data of 2001 to 2014. And the equations were validated with data from 2015 to 2017, finding an R2 greater than 0.8. The efficiency of forcing (EF), which shows a small variation at the top of the atmosphere, is analyzed, but on the surface, there is less efficiency in the dry season compared to the remaining months.